2014
DOI: 10.1111/clr.12368
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue augmentation of ridge defects in the maxillary anterior area using two different methods: a randomized controlled clinical trial

Abstract: OBJECTIVES: To test whether or not vascularized interpositional periosteal-connective tissue grafts are as successful as free subepithelial connective tissue grafts in augmenting volume defects in the anterior maxilla. MATERIAL AND METHODS: Twenty subjects with Seibert class 1 ridge defects in the anterior maxilla were randomly, equally assigned to augmentation by vascularized interpositional periosteal-connective tissue graft (test) or free subepithelial connective tissue graft (control). Clinical periodontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 21 publications
9
48
0
Order By: Relevance
“…, Akcali et al. ). In this study, attached peridental soft tissues were augmented to simulate a mucosal soft tissue volume augmentation procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, Akcali et al. ). In this study, attached peridental soft tissues were augmented to simulate a mucosal soft tissue volume augmentation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Akcali et al. reported of a soft tissue thickness increase after grafting with a free SCTG of edentulous ridges of (median, range) 1 mm, 0.37–1.45 measured directly after soft tissue augmentation and 0.63 mm, 0.28–1.22 after 6 months of healing. The vascularized inter‐positional periosteal‐connective tissue graft showed significant higher thickness increases than the free SCTG (1.21 mm, 0.74–2.47 (after augmentation); 1.18 mm, 0.16–1.75 (after 6 month)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two methods for collecting connective tissue, namely, those for vascularized interpositional periosteal-connective tissue and for free subepithelial connective tissue. A randomized controlled clinical trial by Akcalı et al demonstrated that both soft tissue augmentation techniques were effective in increasing the volume of defective alveolar ridge in the anterior maxilla [72]. However, after 6 months, sites treated with a pediculated graft were superior in terms of maintaining the initially augmented volume and showed less shrinkage of the graft.…”
Section: Soft Tissue Augmentation In Implant Therapymentioning
confidence: 99%